Associated factors of diabetic retinopathy in type 1 and 2 diabetes in Limpopo province in South Africa - Maluleke, Khisimusi Debree; Ntimana, Cairo Bruce; Mashaba, Reneilwe Given; Seakamela, Kagiso Peace; Maimela, Eric (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundDiabetic retinopathy (DR) is the major cause of vision impairment or blindness in individuals who have diabetes. It has accounted for 2.6% of all cases of blindness, and 1.9% of all cases of vision impairments globally. There is a lack of data on the prevalence of diabetic retinopathy and its associated factors amongst diabetic rural populations. Hence, the current study aimed to determine factors associated with diabetic retinopathy (DR) among diabetes mellitus (DM) patients undergoing diabetic therapy.MethodsThe study was cross-sectional in design and the participants were selected using convenient sampling. STATA version 15 software was used for data analysis. Chi-square was used to compare proportions. Logistic regression was used to determine the relationship between DR and associated risk factors.ResultsThe prevalence of DR was 35.3%, of which 32% were mild and 3.4% were moderate non-proliferative DR (NPDR). Females were more unemployed than males (32.1% versus 16.8%, p=0.0058). Males were found to drink alcohol (21.8% versus 1.9%, p<0.001) and smoke cigarettes (4% versus 0.3%, p=0.0034) more than females. Being aged ≥ 55 years (OR: 2.7, 95% CI: 1.6-4.4), with matric qualification (OR: 0.6; 95% CI: 0.4-1.0); employed (OR: 1.4, 95% CI: 1.2-1.6); having high systolic blood pressure (OR=1.4, 95%CI=1.1-1.7) were the independent determinants of DR.ConclusionsThe prevalence of diabetic retinopathy was 34%. DR was determined by high systolic blood pressure, old age, and employment. Although not statistically significant, gender, hyperglycemic state, poor glycemic control, smoking, and increased body mass index (BMI) were associated with increased risk of developing DR.